A solution-based ALD route towards (CH3NH3)(PbI3) perovskite via lead sulfide films. Issue 43 (23rd October 2019) - Koch, Vanessa M.; Barr, Maïssa K. S.; Büttner, Pascal; Mínguez-Bacho, Ignacio; Döhler, Dirk; Winzer, Bettina; Reinhardt, Elisabeth; Segets, Doris; Bachmann, Julien
Abstract : Lead sulfide is deposited from the salts in 'solution ALD' mode and converted directly to the hybrid perovskite CH3 NH3 PbI3 . Abstract : We present a procedure to grow thin films of lead sulfide (PbS) with 'solution Atomic Layer Deposition' (sALD), a technique which transfers the principles of ALD from the gas phase (gALD) to liquid processing. PbS thin films are successfully deposited on planar and porous substrates with a procedure that exhibits the unique ALD characteristics of self-limiting surface chemistry and linear growth at room temperature. The polycrystalline p-type PbS films are stoichiometric and pure. They are converted to the hybrid perovskite methylammonium iodoplumbate (methylammonium lead iodide, MAPI, CH3 NH3 PbI3 ) by annealing to 150 °C in the presence of vapors from methylammonium iodide (MAI).